Prevalence and drivers of human scabies among children and adolescents living and studying in Cameroonian boarding schools - Kouotou, Emmanuel Armand (Parasit Vectors, 2016)
BACKGROUND: The dire lack of information concerning the epidemiology of human scabies in Cameroon, especially in school milieus brought us to undertake the present study which aimed to determine the prevalence and associated factors of scabies in Cameroonian boarding schools. METHODS: A cross-sectional study was conducted from February to March 2015 in four boarding schools in Yaoundé and Buea (Cameroon). Participants were students currently residing in one of the study sites, volunteering to participate in the study and whose parents or guardians had given their consent in this respect. The diagnosis was based on clinical assessment independently performed by two dermatologists. RESULTS: A total of 1,902 students were recruited (50.5 % boys), with a mean age of 14.3 ± 2.5 years. Overall, 338 participants (17.8 %) were diagnosed with scabies. Age ≤ 15 years, male sex, number of students in the school > 500, no access to the school infirmary, sleeping with others, sharing beddings, clothes or toilet stuffs, pruritus in the close entourage and complaining of pruritus were significantly associated with the presence of mites in univariable logistic regression analyses. On the other hand, at least two baths per day, usage of soap for baths and finger nails always cut short appeared as protective factors. After multivariable analysis, male sex (adjusted OR (aOR) 2.06, 95 % CI: 1.40–3.01, P < 0.0001), first cycle level of education (aOR 1.67, 95 % CI: 1.02–2.71, P = 0.040), number of students per dormitory ≤ 10 (aOR 6.99, 95 % CI: 3.34–14.71, P < 0.0001), no access to the school infirmary (aOR 1.62, 95 % CI: 1.12–2.32, P = 0.009) and complaining of pruritus (aOR 93.37, 95 % CI: 60.04–145.19, P < 0.0001) were the independent factors associated with scabies. CONCLUSIONS: The prevalence of scabies was 17.8 %. The male sex, first cycle level of education, a number of students per dormitory ≤ 10, no access to the school infirmary and complaining of pruritus were the independent factors significantly impacting the occurrence of scabies.